Leishmaniose visceral americana em crianças internadas no Hospital Universitário João de Barros Barreto, Belém-Pa: outubro de 2004 a março de 2006 - ARAÚJO, Karina de Nazaré Ferreira de (2022)
The American Visceral Leishmaniasis (AVL), a very prevalent disease among the pediatric age group, represents a risk to this population, since it can evolve to the potentially serious form if not treated appropriately. Considering the always present importance of the knowing the actual state of the disease in kids, this investigation was chosen to be made, whose objective was to describe the clinic-epidemiologic profile of children with AVL admitted to João de Barros Barreto University Hospital (HUJBB), between October 2004 and March 2006. A descriptive study of the transversal type was conducted in kids with ages up to 12 years old admitted to the pediatric infirmary of HUJBB, with confirmed diagnosis of the disease and no previous treatment. The data were gathered from a standard questionnaire applied to the children’s caretakers, with some information also being gathered through reviews of the patients’ records. A free and clear consent term was asked to be signed by all involved. This work was approved by a Human Research Ethics Board. The present sample consisted of 83 patients; of these 53,0% (44/83) were male. According to the age group, the predominance was among 1-3 years old, representing 58,0% (48/83) subjects. All patients came from the state of Pará, and the towns with more cases were Mocajuba and Moju, with 10,8% (9/83) cases each. From January to December 2005, most cases occurred in August, with 13 admittances to the Hospital. It was detected that 66,3% (55/83) of the subjects had contact with animals involved in the transmission chain of the disease before the appearance of the symptoms. Fever, hepatosplenomegaly and the increase of abdominal volume predominated among the clinical manifestations in more than 90% of the cases. Anemia was present in 100% of the cases. The most used diagnosis confirmation method was the mielograma, which diagnosed the presence of leishmania in 84% (59/71) of the cases, followed by the indirect immunofluorescence reaction, with 61,2% (51/83) of them. The results of this study show that the disease maintains its classic natural history. Knowledge of the most frequent clinical of the disease of the American Visceral Leishmaniasis, as well as of the possible locations of disease occurrence, is information that must always be remembered for the differential diagnosis of feverish syndromes accompanied by hepatosplenomegaly, especially in minors originated from rural zones.